Robust Multiperiod Poverty Comparisons - Michael Grimm; Johannes Gräb (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
We propose a methodology for comparing poverty over multiple periods across time and space without arbitrarily aggregating income over various years or relying on arbitrarily specified poverty lines. Following Duclos et al. (2006a), we use the multivariate stochastic dominance methodology to create dominance surfaces for different time spans. We elaborate the method for the bi-dimensional case, using income observed over two periods, one at the beginning and one at the end of a time span, as dimensions. We also embed in this framework a new concept of chronic and transient poverty. We illustrate our approach by performing poverty comparisons using data for Indonesia and Peru.
Keywords: 330; Chronic Poverty; Multiperiod Poverty; Poverty Dominance; Poverty Dynamics; Transient Poverty; Armut; Disparitätsmaß; Soziale Mobilität; Vergleich; Multivariate Analyse; Theorie; Indonesien; Peru